Mycobacterial tlyA gene product is localized to the cell-wall without signal sequence - Kumar, Santosh; Mittal, Ekansh; Deore, Sapna; Kumar, Anil; Rahman, Aejazur; Musti, Krishnasastry V. (Frontiers in Cellular and Infection Microbiology, 2015)
The mycobacterial tlyA gene product, Rv1694 (MtbTlyA), has been annotated as 'hemolysin' which was re-annotated as 2'-O rRNA methyl transferase. In order to function as a hemolysin, it must reach extracellular milieu with the help of signal sequence(s) and/or transmembrane segment(s). However, the MtbTlyA neither has classical signals sequences that signify general/Sec/Tat pathways nor transmembrane segments. Interestingly, the tlyA gene appears to be restricted to pathogenic strains such as H37Rv, M. marinum, M. leprae, than M. smegmatis, M. vaccae, M. kansasii etc., which highlights the need for a detailed investigation to understand its functions. In this study, we have provided several evidences which highlight the presence of TlyA on the surface of M. marinum (native host) and upon expression in M. smegmatis (surrogate host) and E. coli (heterologous host). The TlyA was visualized at the bacterial-surface by confocal microscopy and accessible to Proteinase K. In addition, sub-cellular fractionation has revealed the presence of TlyA in the membrane fractions and this sequestration is not dependent on TatA, TatC or SecA2 pathways. As a consequence of expression, the recombinant bacteria exhibit distinct hemolysis. Interestingly, the MtbTlyA was also detected in both membrane vesicles secreted by M. smegmatis and outer membrane vesicles secreted by E. coli. Our experimental evidences unambiguously confirm that the mycobacterial TlyA can reach the extra cellular milieu without any signal sequence. Hence, the localization of TlyA class of proteins at the bacterial surface may highlight the existence of non-classical bacterial secretion mechanisms.